Single organelle dynamics linked to 3D structure by correlative live‐cell imaging and 3D electron microscopy. (25th March 2018) - Fermie, Job; Liv, Nalan; ten Brink, Corlinda; van Donselaar, Elly G.; Müller, Wally H.; Schieber, Nicole L.; Schwab, Yannick; Gerritsen, Hans C.; Klumperman, Judith
Abstract : Live‐cell correlative light‐electron microscopy (live‐cell‐CLEM) integrates live movies with the corresponding electron microscopy (EM) image, but a major challenge is to relate the dynamic characteristics of single organelles to their 3‐dimensional (3D) ultrastructure. Here, we introduce focused ion beam scanning electron microscopy (FIB‐SEM) in a modular live‐cell‐CLEM pipeline for a single organelle CLEM. We transfected cells with lysosomal‐associated membrane protein 1‐green fluorescent protein (LAMP‐1‐GFP), analyzed the dynamics of individual GFP‐positive spots, and correlated these to their corresponding fine‐architecture and immediate cellular environment. By FIB‐SEM we quantitatively assessed morphological characteristics, like number of intraluminal vesicles and contact sites with endoplasmic reticulum and mitochondria. Hence, we present a novel way to integrate multiple parameters of subcellular dynamics and architecture onto a single organelle, which is relevant to address biological questions related to membrane trafficking, organelle biogenesis and positioning. Furthermore, by using CLEM to select regions of interest, our method allows for targeted FIB‐SEM, which significantly reduces time required for image acquisition and data processing. Abstract : Currently, no correlative light‐electron microscopy strategies exist that can link single organelle dynamics to their 3‐dimensional (3D) ultrastructural characteristics. Fermie et al employ a novel correlative workflow using FIB‐SEM to combine dynamic and 3D ultrastructural information of endolysosomal organelles.